1/6+x=-23/6

Simple and best practice solution for 1/6+x=-23/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6+x=-23/6 equation:


x in (-oo:+oo)

x+1/6 = -23/6 // + -23/6

x+1/6-(-23/6) = 0

x+1/6+23/6 = 0

x+4 = 0 // - 4

x = -4

x = -4

See similar equations:

| d-6=-67/10 | | -6/7m=-36/7 | | -5/11=w-1 | | -6x=12/5 | | b+1=17/12 | | -5/14=x-6/7 | | 14-7x=199-42x | | 5x-3=29 | | w/4=7 | | 2/7t=-16/7 | | t+8=11 | | -89/8=n-1/8 | | m-4=-15 | | m+7=39/5 | | 117/11=w+10 | | 3a=3 | | 6m=18/5 | | b+1=9 | | -4/5+n=-7/5 | | n-3/7=4/7 | | 12-9x=102-44x | | 1/6k=5/33 | | b+2=17/9 | | d+2/9=101/9 | | -1/2m=-9/2 | | 16=b+10 | | -6t=42/11 | | -7w=35/9 | | 4k=-4 | | 1/6+m=1/4 | | 1+k=0 | | -3/4+k=13/4 |

Equations solver categories